Molecular characterization and in-silico analysis of myeloid cathelicidin gene in Swamp buffalo - KALITA, D J; SHARMA, S; BARUA, A (The Indian Journal of Animal Sciences, 2017)
Mammalian cathelicidin is the one of the important antimicrobial peptides expressed by different tissues. Present study was undertaken to characterize the cathelicidin gene of swamp buffalo (Bubalus carabanensis) to know the potency of the predicted peptide for in-silco designing of antimicrobial peptides. Total RNA was isolated from the bone marrow myeloid cells and reverse transcribed the cathelicidin gene by specific primers. The amplified PCR product was purified, cloned and sequenced. The size of the PCR product was 520 bp and cloned cDNA after sequencing revealed the open reading frame (ORF) of 447 bases. The total number of predicted amino acid in the pre-pro-peptide was 148. Alanine at 29 was found to be conserved in most of the congeners and might be the probable site for proteolytic cleavage of the signal sequence. Valine at 130 was common in all most all congeners which revealed the point of termination of pro-sequence from the mature peptide. The antimicrobial activity exists only in C-terminal mature domain from 131-146. Presence of 6 arginine, which inferred more cationicity as well as 3 proline and 5 tryptophan may make this congener more potent antimicrobial peptide. Support vector machine algorithms showed the antimicrobial potency of different segments of the mature peptide. From the present study, it is concluded that the mature domain of the swamp buffalo cathelicidin can be used as template for synthesis of novel antimicrobial agents.